PARTISIPASI MASYARAKAT DALAM PROGRAM BANK SAMPAH SERASI WILAYAH VILA DAGO RW 21 BENDA BARU PAMULANG TANGERANG SELATAN - Akmal Maulziandra; Muhtadi Muhtadi (Jurnal Kommunity Online, 2021)
This study aims to determine participation and benefits in the management of the Serasi Garbage Bank with the formulation of the problem: (1) How does public participation in the management of the Serasi Garbage Bank in Dago Benda Baru Pamulang South Tangerang  (2) What are the benefits of the Serasi Garbage Bank in the Dago Benda Baru Pamulang Tangerang area South. The research methodology conducted by researchers is research conducted through a descriptive qualitative approach. Qualitative research is research that produces analytical procedures that do not use statistical analysis procedures or other quantitative methods, namely data obtained in the form of words, images and behavior. Through the Serasi Garbage Bank program, is a program that establishes and invites the community to manage household waste properly, the Serasi Garbage Bank program is an individual and collective waste management system with the principle of recycling cooperation with business partners.The benefits of managing the Serasi Garbage Bank, on the social aspects of the community, are concerned about waste and the environment. Economic aspects are still relatively small or a little income from weighing but can be an added value for the community. This aspect of the environment becomes cleaner, more beautiful and safer.